2011
DOI: 10.1007/s00011-011-0321-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of α,β-amyrin, a triterpene from Protium heptaphyllum, on cerulein-induced acute pancreatitis in mice

Abstract: α,β-Amyrin ameliorates cerulein-induced acute pancreatitis by acting as an anti-inflammatory and antioxidant agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 47 publications
1
31
0
6
Order By: Relevance
“…Pharmacokinetic investigations with a reliable GC-MS method reveal that amyrin has low bioavailabilty but a long elimination half life, following its oral administration to normal rats [35]. However, earlier works [9-16] show that it is orally effective in several animal models of inflammation, nociception, gastroprotection and hepatoprotection. Also, the present study demonstrates the oral efficacy of alpha, beta-amyrin in reducing hyperglycemia and hyperlipidemia in the experimental models of STZ-induced diabetes and diet induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacokinetic investigations with a reliable GC-MS method reveal that amyrin has low bioavailabilty but a long elimination half life, following its oral administration to normal rats [35]. However, earlier works [9-16] show that it is orally effective in several animal models of inflammation, nociception, gastroprotection and hepatoprotection. Also, the present study demonstrates the oral efficacy of alpha, beta-amyrin in reducing hyperglycemia and hyperlipidemia in the experimental models of STZ-induced diabetes and diet induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated the anti-inflammatory and antioxidant effects of α, β-Amyrin in rodent models of cerulein-induced acute pancreatitis and ligature-induced acute periodontitis [9,10], wherein this triterpenoid was found to significantly inhibit the serum level of pro-inflammatory cytokine TNF- α as well as the increases in myeloperoxidase (MPO) activity and and thiobarbituric acid-reactive substances (TBARS). In the present study, treatment with α, β-amyrin effectively restored the reduced insulin levels seen in streptozotocin-diabetic controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These triterpenes have been reported to exert anti-inflammatory properties in various animal models, including colitis, cystitis or pancreatitis. [7][8][9] In the central nervous system, α-and β-amyrin have been reported to exhibit anti-nociceptive properties via the activation of cannabinoid receptors 10,11) and to exhibit antianxiety or anti-depression properties through the modulation of the benzodiazepine site of the γ-aminobutyric acid type A (GABA A ) receptor or noradrenergic receptor, respectively.…”
mentioning
confidence: 99%
“…It was also demonstrated that the lethal dose of geniposide was 1431.1 mg/kg (Ding et al 2013). In pancreatitis, they greatly suppressed inflammatory cell infiltration, acinar cell necrosis, the expression of TNF-α and the inducible nitric oxide synthase, decreases the serum levels of amylase and lipase and of interleukin IL-6 and the activity of pancreatic mieloperoxidase (MPO) (Melo et al 2010(Melo et al , 2011.…”
Section: Genipa Americana Lmentioning
confidence: 99%